Microenvironments and Cellular Characteristics in the Micro Tumor Cords of Malignant Solid Tumors - Hiroshi Harada (International Journal of Molecular Sciences, 2012)
Because of the accelerated proliferation of cancer cells and the limited distance that molecular oxygen can diffuse from functional tumor blood vessels, there appears to be a unique histology in malignant solid tumors, conglomerates of micro tumor cords. A functional blood vessel exists at the center of each tumor cord and is sequentially surrounded by well-oxygenated, oxygen-insufficient, and oxygen-depleted cancer cells in the shape of baumkuchen (layered). Cancer cells, by inducing the expression of various genes, adapt to the highly heterogeneous microenvironments in each layer. Accumulated evidence has suggested that not only tumor microenvironments but also cellular adaptive responses to them, influence the radioresistance of cancer cells. However, precisely how these factors affect one another and eventually influence the therapeutic effect of radiation therapy remains to be elucidated. Here, based on recent basic and clinical cancer research, we deduced extrinsic (oxygen concentration, glucose concentration, pH etc.) and intrinsic (transcriptional activity of hypoxia-inducible factor 1, metabolic pathways, cell cycle status, proliferative activity etc.) parameters in each layer of a tumor cord. In addition, we reviewed the latest information about the molecular mechanism linking these factors with both tumor radioresistance and tumor recurrence after radiation therapy.